Improving Health Through Diet and Exercise in Children - Rush, E; Coppinger, T (Macmillan Publishers Limited, part of Springer Nature, 2018)
We know that nutritious foods and quality physical activity are two of the fundamental needs for normal growth and development of children. Food based dietary guidelines and physical activity recommendations have universal evidence base but the teaching of fundamental movement skills is limited without support. Given the importance of prevention of childhood obesity the distal drivers also need to be examined including poverty. Interventions trialled in carefully controlled conditions while shown to have efficacy are not effective in the real world. There is a need for more research and rigorous evaluation of interventions in combinations of settings and with innovative research designs rather than the traditional randomised controlled trial of limited duration. What works needs to be defined and measured differently. One example of a 14 year and ongoing physical activity and nutrition intervention, Project Energize in the Waikato region of New Zealand is described along-side innovative measures of effectiveness such as time to run 550m and assessment of dental health. Translation of research findings into public health actions is a challenge alongside the effects of global climate change, trade agreement, multinational companies and the influence of social media in informing people. The need is to take action now, the child cannot wait.